A Comparison of Death Anxiety, Intolerance of Uncertainty and Self-Esteem as Predictors of Social Anxiety Symptoms. Issue 3 (24th September 2019) - Lowe, Juanita; Harris, Lynne M.
Abstract: This study sought to examine the role of death anxiety as a transdiagnostic predictor of social anxiety symptomatology compared to self-esteem and intolerance of uncertainty, and to examine the relationship between measures of intrinsic and extrinsic religiosity and death anxiety. A total of 591 participants, 445 females, average age 38.0 years ( SD = 14.5), completed an online survey including background questions, the Depression, Anxiety and Stress Scale, the Social Interaction Anxiety and Social Phobia Scale, the Rosenberg Self-Esteem Scale, the Intolerance of Uncertainty Scale, the Santa Clara Strength of Religious Faith Questionnaire, the Spirituality Scale, and the Death Anxiety Scale. No significant, independent relationship was found between death anxiety and social anxiety symptomatology, although self-esteem and intolerance of uncertainty were significant predictors of both measures of social anxiety, confirming the importance of these key transdiagnostic mediators as predictors of social anxiety symptomatology. A strong negative correlation was found between death anxiety and measures of both intrinsic and extrinsic religiosity in this general population sample not selected for high religious affiliation.